Providing Support to Relatives and Friends Managing Both Chronic Physical Illness and Depression: the Views of a National Sample of U.S. Adults - Janevic, Mary (2012)
OBJECTIVE: To describe how comorbid depression in chronically ill adults affects the willingness of their family and friends to provide them with illness management support. METHODS: We identified a national sample of U.S. adults (n=1027), all of whom had a close relative or friend with a chronic physical illness. We examined whether respondents were less willing to help their relatives/friends with disease management when they reported that these relatives/friends were also diagnosed with depression. RESULTS: In multivariate models, the odds of respondents being willing to provide disease-management support doubled when the relative/friend was depressed (adjusted odds ratio (AOR) = 1.99; 95% C.I=1.31, 3.02). Respondents were willing to perform an equal number of illness support tasks for relatives/friends with and without depression. However, respondents reported 30% more difficulties discussing health issues (incidence rate ratio (IRR)=1.30; 95% C.I=1.11,1.53), and 44% more barriers to providing support (IRR=1.44; 95% C.I=1.18, 1.75) to depressed relatives/friends. CONCLUSION: U.S. adults are more willing to provide disease-management support for chronically ill relatives/friends with depression. However, helping depressed relatives/friends is also more challenging. PRACTICE IMPLICATIONS: By providing resources for potential supporters, health providers could mobilize an important source of disease-management support for patients with chronic illness and depression.